Actantial Model Analysis in Pulau Akko Episode One “Plastic Waste” - Arsa Widitiarsa Utoyo (INJECT (Interdisciplinary Journal of Communication), 2022)
This exploration plans to dissect the plot structure in Pulau Akko animation movie. Scientists need to discover a few inquiries, what are the plot components, how the plot components establish the plot design of the story, and what sort of plot is utilized in the animation. This examination utilizes A.J. Greimas to enter the field. Information is gathered through perusing, distinguishing proof, understanding, and examination utilizing the techniques and hypotheses utilized in this exploration. The consequence of this exploration is that plot components incorporate opening, story issue, climbing activity, peak, sliding activity and goal. To discover the primary plot structure, this examination separates the capacity of each character into six entertainers, who are sender, collector, subject, item, partner and adversary. At long last, the scientist closed what sort of plot and how the closure of the animation is. The plot of the animation is emotional or chronological plot on the grounds that the story through in sequential request. What's more, the animation is shut plot because the issue of the story is settled.